DEVELOPMENT AND MASTERING OF TECHNOLOGIES OF USE OF METALLIZED PELLETS WITH A HIGH CONTENT OF PHOSPHORUS IN THE ENVIRONMENT OF «BSW – MANAGEMENT COMPANY OF «BMC» - O. M. Grudnitsky; A. V. Feklistov; A. V. Demin; A. I. Rozhkov; V. V. Nikolaev (Литьë и металлургия)
It is shown that it is economically reasonable to use metallized pellets with a high content of phosphorus in the environment of “BMP”, produced in the Bolivarian Republic of Venezuela.